Massage for Eid Travelers in 2019 - Danang Ari Santoso; Wawan Setiawan; Bayu Septa M.T; Mislan; Arya T Candra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2020)
Homecoming activities that occur each approaching Eid certainly make travelers feel exhausted on the way to their hometown. So with that it requires activities that help travelers. In this case we provide a place to rest for travelers and provide free massage for travelers. Massage comes from the French word